MARRIAGE BETWEEN COUSINS: MATRIMONIES OF CONVENIENCE AND CONSANGUINITY IN RURAL SPAIN DURING THE MODERN ERA. - Pulido, Raquel Tovar (Revista de Historia Social y de las Mentalidades, 2024)
This article analyses the matrimonial items from the sacramental books of the Diocese of Avila, the parish registers and the ecclesiastical dispensations. It have been studied the marriages celebrated in the villages of Mombeltrán and Cebreros in the period between 1690 and 1790. It have been focused on the presence of consanguineous links in marriages as well as second marriages. Its study is interesting because it contributes to enrich the historiography on consanguinity in the interior areas of the Iberian Peninsula. It is noticed a concession of matrimonial waivers by the Catholic Church for the celebration of consanguineous marriages, kinship marriages and marriages with doubled bonds of different degree. The brides are singles and widowers who live in rural communities.